2004
DOI: 10.1093/annonc/mdh019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sentinel node biopsy and axillary staging strategy on hospital costs

Abstract: SNB seems to be associated with higher hospital costs than diagnostic ALND. Frozen section diagnosis seems to be worthwhile as long as the false negative rate is <35%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Rónká et al showed that, with respect to hospital costs, FS analysis seems to be worthwhile as long as the false negative rate does not exceed 35% [14]. This is due to the lower costs of a shorter hospital stay and the association with a decrease in long-term postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Rónká et al showed that, with respect to hospital costs, FS analysis seems to be worthwhile as long as the false negative rate does not exceed 35% [14]. This is due to the lower costs of a shorter hospital stay and the association with a decrease in long-term postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in addition to increasing the potential for patient morbidity, there is added financial expense in the staged approach. 7 Completion ALND following autologous reconstruction may pose certain risks toward flap viability. However, a latissimus dorsi myocutaneous flap is not typically used as a primary form of reconstruction (0.5% of the cases in this series), and free tissue transfer is more commonly dependent on internal mammary vessels rather than the thoracodorsal pedicle that may be compromised in a secondary axillary dissection after reconstruction.…”
Section: Annals Of Plastic Surgery • Volume 66 Number 5 May 2011mentioning
confidence: 99%
“…[5][6][7][8] It has been previously reported from this institution that performing SLNB at the time of definitive surgery had minimal impact on the intraoperative reconstructive plan. 9 The purpose of this study was to evaluate both the immediate and long-term outcomes in women who underwent SLNB in the same setting as mastectomy and IBR.…”
mentioning
confidence: 94%
“…Lymphatic mapping with sentinel lymph node (SLN) biopsy has been introduced as an alternative to elective LN dissection and has gained rapid acceptance because it allows improved accuracy and decreased patient morbidity for regional cancer staging (4, 5). However, SLN biopsy still has major limitations.…”
Section: Introductionmentioning
confidence: 99%